Letter - Stolz, George
029-0139-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU St/H TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter No. PAR AVION 8th June 1937. Mr. Walter M. Citrine, LONDON. Dear Comrade Citrine, In immediate reply to your letter of the 7th June, I would inform you that Comrade Schevenels, who came to Paris yesterday from Geneva, has bought fifty Studebaker lorries for the Spanish section of our International Solidarity Fund from M. Georges Moha, who is the Spanish agent for Studebaker. Ten of these lorries are to go out for the use of the Onteniente Hospital, and the remaining forty are to be put into service at the frontier for transporting food, etc., from the frontier to Valencia and Madrid. In sending our wire yesterday, we imagined that the CWS Bank would act in the same way as the Twentsche Bank, Amsterdam, which, in these circumstances, would wire us direct for our confirmation, upon receipt of which it would make the transfer. As however we did not receive a wire from the CWS Bank, we have to-day sent a letter of confirmation by air. Yours sincerely, G.Stolz, Assistant Secretary: 292/946/29/139